2013
DOI: 10.1139/cjfr-2012-0323
|View full text |Cite
|
Sign up to set email alerts
|

Twelve-year responses of planted and naturally regenerating conifers to variable-retention harvest in the Pacific Northwest, USA

Abstract: We studied patterns of conifer regeneration over 12 years as part of a regional-scale experiment in variable-retention harvest in the Pacific Northwest, the DEMO Study. We compared survival and height growth of planted conifers and density and seral composition of natural regeneration among treatments with differing retention levels (15% versus 40%) and patterns (dispersed versus aggregated) replicated across a range of latitudes and forest zones. We also assessed plot-scale relationships of natural regenerati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
20
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 35 publications
4
20
0
Order By: Relevance
“…These results contrast with reductions in stem density and biomass observed in P. tremuloides-dominated systems with 40% basal area retained [38]. However, our results align with findings that retention level (up to 50% basal area retained) had little effect on total or specifically aspen/birch sapling densities [22] and that stem density may be less impacted by retained overstory trees than growth rates [27]. Comparable eucalypt densities and growth rates between harvests with aggregated retention compared to clearcuts also suggests negative impacts on crop tree regeneration may be less of a concern in some systems [60].…”
Section: Discussionsupporting
confidence: 78%
“…These results contrast with reductions in stem density and biomass observed in P. tremuloides-dominated systems with 40% basal area retained [38]. However, our results align with findings that retention level (up to 50% basal area retained) had little effect on total or specifically aspen/birch sapling densities [22] and that stem density may be less impacted by retained overstory trees than growth rates [27]. Comparable eucalypt densities and growth rates between harvests with aggregated retention compared to clearcuts also suggests negative impacts on crop tree regeneration may be less of a concern in some systems [60].…”
Section: Discussionsupporting
confidence: 78%
“…Previous research in stands harvested with partially retained overstories has demonstrated a negative correlation between regeneration growth and understory shrub cover (e.g., Harrington 2006, Mitchell et al 2007, Urgenson et al 2013, Palik et al 2014. Our results seem to support this argument, because we found a negative correlation of current regenerated tree density to both shrub biomass 2 yr and shrub biomass 2-10 yr .…”
Section: Effect Of Understory Vegetation Treatmentssupporting
confidence: 84%
“…The variability in stand conditions prior to restoration treatments was reflected in a high variability in the spatial distribution of advanced regeneration. The species composition and densities of the cohorts that initiated after the restoration treatments were highly variable at small spatial scales [51]. However, the densities of tree regeneration did not differ sufficiently to result in statistically significant differences between treatment averages.…”
Section: Tree Regeneration (Natural)mentioning
confidence: 87%